CdS/ZnS Co-Sensitized Hierarchical TiO2 Nanotree Array with Rutile/Anatase Junctions for Enhanced Photoelectrochemical Performance. Issue 10 (1st January 2016) - Wang, Zhuang; Wang, Xingzhi; Jiang, Xishun; Tao, Jiajia; Gong, Zezhou; Cheng, Yunlang; Zhang, Miao; Yang, Lei; Lv, Jianguo; He, Gang; Sun, Zhaoqi
Abstract : Hetero-structured TiO2 nanotree arrays on flurine-doped tin oxide (FTO) substrates were deposited by a two-step hydrothermal method, CdS/ZnS core-shell quantum dots (CdS/ZnS QDs) were deposited by a successive ionic layer absorption and reaction (SILAR) process. The TiO2 nanotree array is composed of a trunk-branch structure where the trunk is rutile TiO2 nanorod array and the branch is anatase TiO2 nanosheets standing on the trunk. Morphology, optical properties and photoelectrochemical (PEC) performances were investigated in detail. After the deposition of CdS/ZnS QDs, TiO2 nanotree array photoanode shows much better PEC performance compared to TiO2 nanorod array photoanode that sensitized nanotree array show a higher photocurrent desity (1.5 mA/cm 2 ) at 1.0 V and almost 2-fold current density (0.29 mA/cm 2 ) than sensitized nanorod array (1.0 mA/cm 2 and 0.15 mA/cm 2 ) in the measurement of linear sweep voltammetry (LSV) and transient photocurrent, respectively. This result is due to the enlarged surface specific area for more quantum dots loading, and also due to the rutile/anatase junctions formed on the boundary of trunks and branches, leading to an effective charge separating and transporting. It suggests that the hetero-structured TiO2 nanotree array is very promising to be applied in highly efficient photoanodes for energy devices.